The Urgency of Artificial Intelligence Utilization in Contemporary Warfare - Putra, Hendriman; Mulyono, Budi Eko (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This article aims to analyze the urgency of implementing artificial intelligence (AI) in supporting contemporary military operations. This study employs a qualitative descriptive method by analyzing related literature, government policies, and case studies of AI applications in the military domain. The research findings indicate that AI has the potential to significantly enhance the efficiency, accuracy, and effectiveness of military operations. The application of AI can encompass various fields such as intelligence analysis, mission planning, weapons system control, logistics, and training simulation. However, the development and implementation of AI must also consider ethical, security, and regulatory aspects.